Accidence and acronyms: deploying electronic assessment in support of classical language teaching in a university context - Ashdowne, R (Sage Publications, 2009)
This article describes the process of design and implementation of GALACTICA ('Greek And Latin Accidence Consolidation Training, Internet-Centred Assessment') in support of the University of Oxford's Classics Faculty language consolidation classes. The context and aims of the previous paper-based 'assessment' system are considered (being unusual in an university setting) and their significance for the move to an electronic system are addressed: student motivation for revision of basic grammar was the prime aim, and this is retained and enhanced with the electronic system while valuable class time is freed up for language instruction. Technical issues relating to assessment in classical languages and in the Oxford set-up are highlighted and their resolution outlined, while questions regarding potential problems (with cheating, etc.) are also dealt with.